2020
DOI: 10.1111/dth.13884
|View full text |Cite
|
Sign up to set email alerts
|

Mental health assessment of frontline COVID ‐19 dermatologists: A Pan‐Indian multicentric cross‐sectional study

Abstract: Following the outbreak of COVID-19 pandemic, health care workers are involved in screening, investigations, admission, ward rounds, and even performing life-resuscitating procedures. 1 Dermatology residents, young faculties, and consultants are not used to handling long hours of duty and stressful environment. 2 We evaluated the mental health status of front-line dermatologists combating the pandemic. This was a cross-sectional, observational study. Dermatologists engaged in direct patient contact through clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“… Other causes reported include financial crisis, loneliness, social boycott and pressure to be quarantined, being COVID-19 positive, COVID-19 work-related stress, unable to come back home after the lockdown was imposed, and unavailability of alcohol. 18 Mental Health Assessment of Frontline COVID ‐19 Dermatologists: A Pan‐Indian Multi-centric Cross-sectional Study ( Sil et al, 2020 ) Healthcare workers (Dermatologists); n = 41; Online survey; Cross-sectional study Depression, stress The overall prevalence of depression and stress was 26.82% and 29.2%, respectively. Being female, age >30 years, and staying away from family, were significantly associated with moderate-severe depression.…”
Section: Resultsmentioning
confidence: 99%
“… Other causes reported include financial crisis, loneliness, social boycott and pressure to be quarantined, being COVID-19 positive, COVID-19 work-related stress, unable to come back home after the lockdown was imposed, and unavailability of alcohol. 18 Mental Health Assessment of Frontline COVID ‐19 Dermatologists: A Pan‐Indian Multi-centric Cross-sectional Study ( Sil et al, 2020 ) Healthcare workers (Dermatologists); n = 41; Online survey; Cross-sectional study Depression, stress The overall prevalence of depression and stress was 26.82% and 29.2%, respectively. Being female, age >30 years, and staying away from family, were significantly associated with moderate-severe depression.…”
Section: Resultsmentioning
confidence: 99%
“…14 Two studies on mental health of Indian dermatologists were published recently but included only frontline dermatologists in quarantined environments. 15,16 Our study addresses several mental health conditions in COVID-19 dermatologists on a large scale, taking into account demographic data, that is, location (continent), practice setting and population density, and practice years. We performed comparative analyses to identify clinically meaningful associations of mental distress in dermatologists during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Dermatology is considered a non‐emergency specialty and, hence, mental health concerns often remain under‐addressed 14 . Two studies on mental health of Indian dermatologists were published recently but included only frontline dermatologists in quarantined environments 15,16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pooled prevalence of depressionTwenty-eight studies reported the prevalence of depression during COVID-19 in different samples from South Asian countries[47][48][49][52][53][54][57][58][59][60][62][63][64][65][66][67][69][70][71][72][73][74][75][76][77][78][79][80] . The Patient Health Questionnaire (PHQ)-9 was the most frequently used instrument (n = 11), followed by Depression, Anxiety and Stress Scale -21 Items (DASS-21) scales (n = 9), Hospital Anxiety and Depression Scale (HADS) (n = 4), Center for Epidemiologic Studies Depression Scale (CES-D) (n = 2), Patient Health Questionnaire-4 (PHQ-4) (n = 1), and Self Reporting Questionnaire 20-items (SRQ-20) scale (n = 1).…”
mentioning
confidence: 99%